Model of Positivization of Shari'ah Economic Law in Indonesia: A Study of Bank Indonesia Regulations 2008-2023 - Ahmad Munif; Nur Hasan; Siti Tatmainul Qulub (Universitas Wahid Hasyim Semarang, 2024)
The objective of this article is to clarify the regulations established by Bank Indonesia (PBI) from 2008 to 2023 in relation to sharia-compliant banking. PBI represents a regulatory framework incorporating or referencing the Fatwa DSN-MUI, as mandated by the Law on Banking Regulations for Islamic Banking, which requires that the Fatwa DSN-MUI serve as a reference point for the principles of Islamic banking. This study aims to address two research questions. The first question concerns the transformation of the DSN-MUI fatwa into a PBI from 2008 to 2023. The second question is an examination of the patterns of transformation. This research is a qualitative study within the field of normative legal research. The primary object of study in this research is the legal materials, namely the PBI and SEBI, which are placed in juxtaposition with the DSN-MUI Fatwa. A content analysis of the regulations was conducted, employing a conceptual approach to identify points of convergence between the PBI and the DSN-MUI fatwa. The findings reveal that the manner in which the DSN-MUI fatwa was transformed into a PBI is evident in both stylistic and substantive aspects. A variety of terms were employed to describe the contracts and the substance of the DSN-MUI fatwas, which were subsequently developed in the PBI. The pattern of transformation of the Fatwa DSN-MUI into the PBI can be identified through the analysis of three distinct patterns: the